2012
DOI: 10.1186/1746-6148-8-90
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high contents of dietary animal-derived protein or carbohydrates on canine faecal microbiota

Abstract: BackgroundConsiderable evidence suggests that food impacts both the gastro-intestinal (GI) function and the microbial ecology of the canine GI tract. The aim of this study was to evaluate the influence of high-carbohydrate (HC), high-protein (HP) and dry commercial (DC) diets on the canine colonic microbiota in Beagle dogs. Diets were allocated according to the Graeco-Latin square design. For this purpose, microbial DNA was isolated from faecal samples and separated by density gradient centrifugation, resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 34 publications
5
64
1
3
Order By: Relevance
“…As opposed to FM samples, Lachnospiraceae and Erysipelotrichaceae (both belong to Firmicutes) were the dominant groups in CF and SG samples. We found a significant positive correlation between these two groups, which is in good agreement with the positive correlation between the proportions of Lachnospiraceae and Erysipelotrichaceae and plant‐based diets observed in many mammals, including humans (Hang et al., ; Hayashi, Sakamoto & Benno, ; Thoetkiattikul et al., ). Lachnospiraceae are a butyrate‐producing superfamily (including Clostridium XIVa and IV subgroups) whose genomes contain numerous genes belonging to a large number of CAZyme families, including members of GH and PL families, which can break down a wide variety of complex carbohydrates found in plants, which are usually indigestible for animals (Biddle, Stewart, Blanchard & Leschine, ; Thoetkiattikul et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…As opposed to FM samples, Lachnospiraceae and Erysipelotrichaceae (both belong to Firmicutes) were the dominant groups in CF and SG samples. We found a significant positive correlation between these two groups, which is in good agreement with the positive correlation between the proportions of Lachnospiraceae and Erysipelotrichaceae and plant‐based diets observed in many mammals, including humans (Hang et al., ; Hayashi, Sakamoto & Benno, ; Thoetkiattikul et al., ). Lachnospiraceae are a butyrate‐producing superfamily (including Clostridium XIVa and IV subgroups) whose genomes contain numerous genes belonging to a large number of CAZyme families, including members of GH and PL families, which can break down a wide variety of complex carbohydrates found in plants, which are usually indigestible for animals (Biddle, Stewart, Blanchard & Leschine, ; Thoetkiattikul et al., ).…”
Section: Discussionsupporting
confidence: 89%
“…Additionally, we reported Coriobacteriales in dog faeces: a finding that was reported in only one other recent study [36]. The hypothesis for the current study was that the high protein greaves-meal diet influences the measured faecal parameters, as it was found to remarkably increase the faecal populations belonging to the order Fusobacteriales [32]. Therefore, our aim was to study whether the effect of dietary greaves-meal and maize starch on faecal microbiota can be associated with altered faecal characteristics, VFAs, and canine faecal calprotectin.…”
Section: Introductionsupporting
confidence: 61%
“…The current study is the hitherto unreported part of a previously published study [32], in which we investigated the effects of the above mentioned diets on canine faecal microbiota. In that study, we found that faecal samples from the greaves-meal diet fed, dogs favoured growth of species of Fusobacteriales .…”
Section: Introductionmentioning
confidence: 99%
“…These data support the hypothesis that microbial changes associated with increased protein in the large bowel include increased numbers of proteolytic bacteria, which result in increased production of ammonia and sulfur containing compounds that are detrimental to bowel health. Microbial population shifts in response to dietary protein load have been demonstrated in cats [16] and dogs [17], [20]. There was also a positive benefit for dogs and cats on stool quality if foods had greater amount of fiber delivered to the large bowel.…”
Section: Discussionmentioning
confidence: 98%